Improvements in dizziness and imbalance results from using a multi disciplinary and multi sensory approach to Vestibular Physical Therapy – a case study - Gottshall, Kim R.; Sessoms, Pinata H. (Frontiers in Systems Neuroscience, 2015)
This paper discusses a case study of a 41 year old active duty male service member who sustained a motorcycle accident and head trauma and underwent multidisciplinary vestibular physical therapy for treatment. He was initially treated with traditional physical therapy applications of treadmill walking and standing balance with some symptom improvements, but was not able to maintain a running speed that would allow him to remain on active duty status. Further treatment utilizing a Computer Assisted Rehabilitation Environment (CAREN) was performed in order to increase difficulty levels and recover more functionality. This treatment is able to elicit vestibular deficits seen in the community as it requires subjects to walk and balance while performing tasks within a virtual scenario with platform motion, visual surround and flow, and cognitive processing. After six weeks of therapy, twice weekly, improvements in clinical vestibular measures were observed as well as walking speed and patient confidence. The subject was able to return to full duty after treatment. This case study provides supportive evidence that multidimensional tasking in a virtual environment provides a safe but demanding form of vestibular therapy for patients needing more challenging tasks than those provided with traditional therapy techniques. Those persons requiring higher levels of performance before returning to work (e.g. pilots, special operators, etc.) may find this type of therapy beneficial.